Vibration engineering and technology of machinery : proceedings of the X International Conference on VETOMAC-V, 27-28, August 2009, Wuhan, P.R. China /: proceedings of the X International Conference on VETOMAC-V, 27-28, August 2009, Wuhan, P.R. China. ([2015]) - Unknown
No abstract available